We Have Buried Our Tomahawks Very Deep in the Ground and in the Sky: Rock River Ho-Chunk Peacekeeping in the 1832 "Black Hawk War". Issue 3 (17th May 2022) - Tronnes, Libby
Abstract: In Spring 1832, a Ho-Chunk delegation attempted to resolve a refugee crisis that threatened to bring war with the Americans into their lands. The return migration of a removed multiethnic band made up primarily of Sauk and Fox families into northern Illinois precipitated a conflict known as the Black Hawk War. When direct diplomacy failed, Rock River Ho-Chunks attempted to spare the lives of their refugee kin while also protecting their cornfields from American invaders. The federal government used the crisis to force a land cession and removal treaty. Nineteenth-century American observers, and historians ever since, have generally overlooked the imaginative peacekeeping strategies deployed by the Ho-Chunk people, schemes designed to prevent troops from finding the refugees and from destroying raised field agriculture. They almost succeeded. Emphasizing Native voices and actions in the historical record and questioning accounts published by the White conflict veterans on which historians traditionally rely allows a new history of this tragic crisis that privileges Native autonomy, ingenuity, and survivance.